Techniques Engineering as a Partial Requirement for the Degree of B.Sc. in Medical Instrumentation Techniques Engineering - Mohammed Mahmoud, Mohammed Ibrahim; Abdullah saleh, Nouralhuda salem; Hassan Bjaj, Hassan Hatem; Jassim Abdul, Mustafa Hisham; Majeed Hindi, Mustafa Khaled (American Journal of Botany and Bioengineering, 2025)
This project was designed specifically for Alzheimer’s patients and serves as a guide for the patient. Through it, one of the patient’s caregivers is controlled if the device sends the patient’s direct location via text message to the Alzheimer’s patient’s caregiver.